Analisis Kebutuhan Pembelajaran Berbasis Problem Based Learning dengan Konteks Tradisi Budak Ngambek Timah pada Siswa Sekolah Dasar Negeri 8 Namang - Ropita, Ropita; Hendrik, Maulina; Martahayu, Vika (Jurnal Humanitas: Katalisator Perubahan dan Inovator Pendidikan, 2026)
Learning practices in primary schools continue to show limitations in implementing contextual and student-centered learning despite the adoption of the Merdeka Curriculum. Instructional practices remain dominated by conventional approaches and have not integrated local socio-cultural contexts as part of the learning process. This study aims to analyze the learning needs for Problem Based Learning incorporating the Budak Ngambek Timah tradition among fourth-grade students at SD Negeri 8 Namang. A qualitative approach with a descriptive design was employed. The research participants included fourth-grade teachers, fourth-grade students, and the school principal. Data were collected through observation, semi-structured interviews, and documentation, and analyzed using the Miles and Huberman model, which comprises data condensation, data display, and conclusion drawing and verification. The findings indicate that PBL has been recognized by teachers and included in instructional planning; however, its implementation has not been conducted systematically and remains focused on textbook-based instruction. Learning activities have not utilized local social and cultural contexts as learning resources. In addition, students demonstrate strong connections to tin mining activities as part of their families’ social and economic realities; however, these experiences have not been used as a foundation for learning. In terms of learning resources, instruction is still dominated by textual materials and is not supported by contextual resources based on local culture. Overall, the findings reveal a gap between the demands of the Merdeka Curriculum, student characteristics, and classroom learning practices.